INFLUENCE OF SCHOOL SUPERVISORS’ ADHERENCE TO ETHICAL PRINCIPLES ON THE REALIZATION OF SUSTAINABLE DEVELOPMENT GOAL 4 (QUALITY EDUCATION) IN PUBLIC SECONDARY SCHOOLS IN NIGERIA. (Journal of Association of Educational Management and Policy Practitioners, 2026)
This study examined how school supervisors' adherence to ethical principles influences the achievement of Sustainable Development Goal 4 quality education in Nigeria’s public senior secondary schools. It was also found based on the concepts that ethical leadership significantly enhances effective school supervision, while strict adherence to professional codes fosters trust and respect. Supervisory practices rooted in equity and non-discrimination promoted inclusive education. Moreover, accountability in monitoring teaching quality improved learning outcomes. Ethics in resource management ensured fair allocation and minimized waste. Supervisors who encouraged safe and inclusive environments strengthened student engagement. Transparent communication and constructive feedback built stakeholder confidence. Finally, commitment to continuous professional development enriched supervisory skills. The study therefore concluded that supervisors who model ethical conduct contribute directly to achieving SDG 4 by fostering a supportive, fair, and high-performing educational system. Ethical adherence in school leadership is thus essential for sustainable educational progress in Nigeria. The also suggested among others that school supervisors should be guided by clear ethical values to foster fair practices that promote inclusive learning, ensure quality teaching, and ultimately drive the attainment of SDG 4 in Nigeria’s public senior secondary schools and ethical leadership in school supervision should be anchored in honesty, fairness, and responsibility, which should be used to build trust among staff and learners, improving school outcomes and promoting sustainable educational progress.